Making a case for using γδ T cells against SARS-CoV-2. (1st November 2020) - Yazdanifar, Mahboubeh; Mashkour, Narges; Bertaina, Alice
Abstract: Intensive worldwide efforts are underway to determine both the pathogenesis of SARS-CoV-2 infection and the immune responses in COVID-19 patients in order to develop effective therapeutics and vaccines. One type of cell that may contribute to these immune responses is the γδ T lymphocyte, which plays a key role in immunosurveillance of the mucosal and epithelial barriers by rapidly responding to pathogens. Although found in low numbers in blood, γδ T cells consist the majority of tissue-resident T cells and participate in the front line of the host immune defense. Previous studies have demonstrated the critical protective role of γδ T cells in immune responses to other respiratory viruses, including SARS-CoV-1. However, no studies have profoundly investigated these cells in COVID-19 patients to date. γδ T cells can be safely expanded in vivo using existing inexpensive FDA-approved drugs such as bisphosphonate, in order to test its protective immune response to SARS-CoV-2. To support this line of research, we review insights gained from previous coronavirus research, along with recent findings, discussing the potential role of γδ T cells in controlling SARS-CoV-2. We conclude by proposing several strategies to enhance γδ T cell's antiviral function, which may be used in developing therapies for COVID-19.